2014
DOI: 10.1088/1367-2630/16/11/113014
|View full text |Cite
|
Sign up to set email alerts
|

Transparent-conductive-oxide (TCO) buffer layer effect on the resistive switching process in metal/TiO2/TCO/metal assemblies

Abstract: The effect of a transparent conductive oxide (TCO) buffer layer on the insulator matrix and on the resistive switching process in the metal/TiO 2 /TCO/metal assembly was studied depending on the material of the TCO (ITO-(In 2 O 3 ) 0.9 (SnO 2 ) 0.1 or SnO 2 or ZnO). For the first time electro-physical studies and near edge x-ray absorption fine structure (NEXAFS) studies were carried out jointly and at the same point of the sample, providing direct experimental evidence that the switching process strongly infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Note that earlier [33] the possibility of switching in the air in all the studied samples was confirmed by implementing the resistive switching in a specially designed box under a nitrogen atmosphere. The resistive switching processes were shown to be almost identical in ambient and nitrogen atmosphere.…”
Section: Experimental Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Note that earlier [33] the possibility of switching in the air in all the studied samples was confirmed by implementing the resistive switching in a specially designed box under a nitrogen atmosphere. The resistive switching processes were shown to be almost identical in ambient and nitrogen atmosphere.…”
Section: Experimental Methodssupporting
confidence: 60%
“…Earlier [33] we revealed that metal/TCO/TiO 2 (TCO is a transparent conducting oxide) assemblies demonstrate the memristor effect after synthesis (without additional annealing) that provides progress towards understanding the nature of the memristor effect. Also it was established that after the switching process these structures can be retained for a long time.…”
Section: Introductionmentioning
confidence: 87%
“…In case of the Ag/Al 2 O 3 /ITO heterostructures studied here, both migration Ag ions and oxygen vacancies are likely contributors to transport and device operation. Indeed, it has been previously demonstrated that ITO layers incorporated in a memristive device can absorb or provide oxygen vacancies under an applied bias . Furthermore, one may imagine that the change in ionic concentration at the ITO/Al 2 O 3 interface may be dictating the observed optical modulation.…”
mentioning
confidence: 99%
“…The increase in the conductivity can be seen in the ZRA where the current is high without UV‐light. Moreover, the OCP measurement for TiO 2 on Ti show the voltage drop in the dark, which is closer to the base level compared to other samples, indicating much less charge accumlation .…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, the Al 2 O 3 can reduce and limit vacancies formed in the TiO 2 coating due to a conductive substrate . The Al 2 O 3 layer is known to be an insulator with a wide bandgap . The bandgap of amorphous anodic Al 2 O 3 layer is found to be 5.1–7.3 eV .…”
Section: Discussionmentioning
confidence: 99%